The significance of green exercise for the health and wellbeing of Italian immigrants in Norway: a mixed-methods study - Giovanna Calogiuri; Evi Petersen; Alessio Rossi; Laura Terragni (BMC, 2023)
Abstract Background Green exercise (physical activity in presence of nature) has beneficial effects for health and wellbeing. Green exercise is a popular form of recreation in the Nordic countries, but participation is lower among the immigrant population from non-Western countries. However, no attention has been given to immigrants from the European Economic Area regarding this topic. Given the cultural and structural differences that surround green exercise in Italy and Norway, the case of the Italian immigrants in Norway is of interest to enrich our understanding of green exercise and its significance for health and wellbeing among immigrants in the Nordic countries. Methods This convergent mixed methods study investigated the pathways that link green exercise to health and wellbeing among Italian immigrants in Norway. Quantitative data were collected through an online survey (n = 321), which was oversampled to better reflect the sociodemographic profile of the reference population. Logistic regression was used to model the association of green exercise with self-rated health (SRH) or satisfaction with life (SWL) before and after controlling for selected confounders (age, gender, educational level, language proficiency, social support, and childhood experiences with green exercise). Qualitative data were collected through semi-structured in-depth interviews (n = 14) and analysed thematically. Merging of the two strands was done using a simultaneous bidirectional approach. Results The logistic regression found a significant bivariate association of green exercise with both SRH and SWL, though the association remained significant only for SWL after controlling for confounders. From the thematic analysis, three themes were identified: Green exercise opportunities contributing to overall satisfaction, Closeness to nature, and Embracing a new lifestyle. The integrated findings indicate that green exercise supported the immigrants' wellbeing, especially by providing stress relief, though socioeconomic status and acculturation may have a major impact on general health. Familiarity, appreciation of nature benefits, social support, and acculturation were identified as facilitating factors. Conclusions This study provides novel insights into how green exercise supports health, wellbeing, and inclusion among immigrants to the Nordic countries and emphasizes the importance of developing culturally adapted strategies to enhance this health-promoting activity among immigrant populations.